Current opinions regarding care of the mature pediatric urology patient. Issue 5 (October 2015) - Szymanski, K.M.; Misseri, R.; Whittam, B.; Large, T.; Cain, M.P.
Summary: Introduction: With continued improvements in pediatric urology care of patients with complex congenital genitourinary conditions, many survive into adulthood. This fact has created a challenging situation of transitioning from pediatric to adult care. Establishing long-term follow-up with appropriate specialists is a critical part of a successful transition to adulthood for this population. Objective: This study sought to elucidate current practices and opinions regarding the management of adult complex genitourinary patients by pediatric urologists, in order to determine if a consensus for adult care exists. Study design: An anonymous, 15-question online survey was created to address practice patterns and opinions regarding the transition of care of complex genitourinary patients. An invitation to participate was distributed via email to 200 pediatric urologists who were members of the American Urological Association. Complex genitourinary patients were defined broadly as those with a history of: spina bifida, bladder exstrophy, cloacal exstrophy, cloacal anomalies, posterior urethral valves or disorders of sex development. Fisher's exact test was used for analysis. Results: The response rate was 31.0% (62/200). Two-thirds (67.7%) cared for adults with complex genitourinary conditions. Overall, 51.6% of pediatric urologists felt that general urologists best follow adult patients, but only 6.5% recommended this for patients with prior complex genitourinary reconstruction ( P  < 0.001). Instead, the majority (80.6%) felt that a pediatric or adult urologist with an interest and training in adolescent/transitional urology who routinely performs such procedures would provide optimal care. Follow-up by a primary care physician alone was not recommended. Recommendations did not change if patients had developmental delay or lived independently ( P  = 0.47 and P  = 0.72, respectively). Overall, 69.4% would refer mature complex genitourinary patients to a urologist with interest and training in adolescent/transitional urology, if one was available. However, only 45.2% had such an individual available in their practice ( P  < 0.001). Discussion: In the present study, the opinions of pediatric urologists regarding optimal providers of long-term follow-up for mature complex genitourinary patients were presented. While the results may not represent the views of the entire pediatric urology community, responses from motivated individuals with a particular interest in transition care may be especially valuable. Although the present study did not outline a mechanism for improving transitional care, it offered valuable information on prevailing opinions in this area. Finally, the opinions of mostly North American Pediatric Urologists were presented, which may not apply to other healthcare settings. Conclusions: Pediatric urologists appeared to be virtually unanimous in recommending that urologists provide the most appropriate long-term follow-up of patients with congenital genitourinary conditions. Specifically, 80% recommended that patients with prior complex surgical reconstruction be followed by a urologist with specific interest, training and experience in the area of transitional urology. The data suggest that this may be an unmet need of these specialists and may signify the need for specific training in the care of such patients.